Factors Causing Students’ Speaking Anxiety in EFL Classrooms at English Education Study Program of Jambi University - Julia Indriyani; Rosinta Norawati; Reli Handayani (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study investigates levels and the factors contributing to students’ speaking anxiety in English as a Foreign Language (EFL) classrooms at the English Education Study Program, Jambi University. Using a quantitative descriptive method, data were collected from 69 fourth-semester students through a Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire. Findings revealed that most students experienced a moderate level of speaking anxiety (42%), followed by high (32%) and low (26%) levels. Communication apprehension emerged as the dominant anxiety factor, followed by test anxiety and fear of negative evaluation. The results highlight the need for language educators to develop supportive classroom environments and implement anxiety-reducing pedagogical strategies. Implications for EFL teachers and future researchers are discussed